2021
DOI: 10.1038/s41598-021-81189-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression and correlation analysis of miRNA–mRNA profiles in swine testicular cells infected with porcine epidemic diarrhea virus

Abstract: The variant virulent porcine epidemic diarrhea virus (PEDV) strain (YN15) can cause severe porcine epidemic diarrhea (PED); however, the attenuated vaccine-like PEDV strain (YN144) can induce immunity in piglets. To investigate the differences in pathogenesis and epigenetic mechanisms between the two strains, differential expression and correlation analyses of the microRNA (miRNA) and mRNA in swine testicular (ST) cells infected with YN15, YN144, and mock were performed on three comparison groups (YN15 vs Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…Similarly, several studies were also mapped to precursor/mature miRNAs of chicken or other animals in miRbase to annotate conserved miRNAs ( Cui et al., 2018 ; Wu et al., 2018 ; Wu et al., 2019a ; Yang et al., 2020 ). In addition, miRNA length showed that the majority had a length of 23 nt and the first nucleotide base revealed U predominance in the identified miRNAs ( Figure 2 ), which is consistent with the findings of other studies ( Chen et al., 2021 ; Zhang et al., 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, several studies were also mapped to precursor/mature miRNAs of chicken or other animals in miRbase to annotate conserved miRNAs ( Cui et al., 2018 ; Wu et al., 2018 ; Wu et al., 2019a ; Yang et al., 2020 ). In addition, miRNA length showed that the majority had a length of 23 nt and the first nucleotide base revealed U predominance in the identified miRNAs ( Figure 2 ), which is consistent with the findings of other studies ( Chen et al., 2021 ; Zhang et al., 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…PEDV is a coronavirus that causes acute and highly contagious intestinal infectious diseases in piglets [28]. PEDV infection leads to dynamic changes of miRNA expression in the host cells and forms a complex interaction network with the virus [29,30]. In recent years, the use of high-throughput sequencing techniques to reveal the integration of miRNAs and mRNAs in viral infection has proven to be helpful in elucidating the regulatory mechanism of miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, downregulating Forkhead box other 1 ( FOXO1 ) expression eventually leads to decidua damage [ 28 ]. The Rap1 signaling pathway is a crucial immune-related pathway and cancer-related pathway [ 29 , 30 ]. The expression of cell adhesion molecules is critical for embryo implantation and pregnancy establishment [ 31 ].…”
Section: Discussionmentioning
confidence: 99%